The Effect of Americanization on the Earnings of Foreign-born Men - Chiswick, Barry R. (Journal of Political Economy, 1978)
The earnings of foreign-born adult white men, as reported in the 1970 Census of Population, are analyzed through comparisons with the native born and among the foreign born by country of origin, years in the United States, and citizenship. Differences in the effects of schooling and postschool training are explored. Although immigrants initially earn less than the native born, their earnings rise more rapidly with U.S. labor market experience, and after 10 to 15 years their earnings equal, and then exceed, that of the native born. Earnings are unrelated to whether the foreign born are U.S. citizens.